2021
DOI: 10.1177/1078155220983413
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge assessment and barriers to cancer screening among Ghanaian community pharmacists

Abstract: Introduction Though there are controversies, cancer screening has been suggested to decrease mortality. Over the years, the most accessible primary healthcare provider; the community pharmacist, has developed an interest in being part of cancer screening activities and prevention of a wide range of other non-communicable diseases. To achieve this, community pharmacists need a working knowledge of the basic screening test and recommendations. Also, it’s important to acknowledge the barriers that may prevent the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…For the respondents in this study, a lack of interest in cancer treatment was not perceived as a barrier among pharmacy staff when counseling cancer patients/survivors. This study showed that the largest barrier when counseling cancer patients/survivors was a lack of relevant training and training materials, reconfirming the results from previous studies [13,24]. Moreover, the lack of a guideline for communicating with cancer patients was also reported as a barrier.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…For the respondents in this study, a lack of interest in cancer treatment was not perceived as a barrier among pharmacy staff when counseling cancer patients/survivors. This study showed that the largest barrier when counseling cancer patients/survivors was a lack of relevant training and training materials, reconfirming the results from previous studies [13,24]. Moreover, the lack of a guideline for communicating with cancer patients was also reported as a barrier.…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, there would be a need for, e.g., campaigns to raise the awareness of the community pharmacies' role or a cross-sectoral collaboration where the hospital will inform patients about how the community pharmacies can contribute to cancer care. Another barrier reported in this study, as well as in a previous study [13], was that community pharmacies focus on other healthcare problems rather than cancer, which might contribute to difficulty in changing public opinions about the role of pharmacies in healthcare. A reason for this focus in Denmark could be that cancer medication is dispensed at the hospital and not at community pharmacies.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Although we are filled with remorse for the delay in handling this delicate health issue, our results will hopefully pave the way for change and improvement, because they clearly reveal limited adherence to the screening schedule in our society. These limitations have been ascribed to several risk factors including, but not limited to, restricted access to and availability of screening services, some beliefs, difficulty specifying the focused target women, inadequate monitoring and evaluation of screening programs, and a health service system that is overwhelmed by health demands [11][12][13]. Despite the growth of community awareness of cervical cancer and the launch of cervical screening programs and the HPV vaccine, knowledge and awareness remain static on the low side of the curve, weighed down by fears relating to speculum examination, discomfort with male health workers, and limited spousal approval, all of which have been identified as additional factors contributing to suboptimal screening rates [14,15].…”
Section: Discussionmentioning
confidence: 99%